2021
DOI: 10.1680/jensu.20.00065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of meta-heuristic algorithms in optimum operation of a single-reservoir dam system

Abstract: Multi-objective models must be built to optimise the use of water supplies. In this study, the performance of the farmland fertility algorithm (FFA) and that of the Harris hawks optimisation (HHO) algorithm were evaluated and compared with each other to solve the two-objective problem of optimal operation of the Golestan dam reservoir under baseline (April 2006 to October 2018) and climate change conditions (April 2021 to October 2033) in Golestan Province, Iran. The operation rules were extracted by minimisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It was found that HHO was among the top performing models in the study in terms of objective value function, CPU run-time, and convergence rate. The usage of HHO in dam reservoir operation optimization has also been found in studies by Donyaii et al (2021) and Nguyen et al (2021). Although studies on WOA, LFWOA, and HHO in dam reservoir operation optimization are currently limited, these algorithms have been demonstrated to produce good performances in other fields.…”
Section: Introductionmentioning
confidence: 85%
“…It was found that HHO was among the top performing models in the study in terms of objective value function, CPU run-time, and convergence rate. The usage of HHO in dam reservoir operation optimization has also been found in studies by Donyaii et al (2021) and Nguyen et al (2021). Although studies on WOA, LFWOA, and HHO in dam reservoir operation optimization are currently limited, these algorithms have been demonstrated to produce good performances in other fields.…”
Section: Introductionmentioning
confidence: 85%
“…e vertical range of the aquifer can be further disrupted by variations in hydraulic conductivity (hydraulic conductivity multiplied by saturated aquifer thickness). Hydraulic characteristics or other elements that have a significant positive or negative influence on groundwater modelling are of higher importance in the modelling [8]. e specific yield ranges between 0.02 and 0.2.…”
Section: Optimizing Parameters Using the Hho Algorithmmentioning
confidence: 99%
“…To consider the multiobjective existence of groundwater systems, one approach is to specify multiple optimization objective functions that quantify different characteristics of system action. ey employ a multiobjective optimization tool to find a collection of nondominated solutions named as Pareto best approaches [8,9]. e Pareto solutions reflect trade-offs among various incomputable and often competing goals, with the property that switching from one solution to another improves one while deteriorating one or more others [10].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the best-worst fuzzy multi-criteria decision model in Lingo9 software was developed by collecting the opinions of 23 GRP experts, based on three general criteria of change in administrative structure (C1), policy structure (C2) and modification of GRP legal structure (C3), which includes 18 sub-criteria. Donyaii et al (2021) evaluated and compared the performance of the farmland fertility algorithm (FFA) and that of the Harris hawks optimization (HHO) algorithm with each other to solve the two-objective problem of optimal operation of the Golestan dam reservoir under baseline (April 2006-October 2018 and climate change conditions (April 2021-October 2033) in Golestan Province, Iran and the results showed that when considering a constant value of the reliability index (i.e. 80%), the rate of vulnerability changes in the multi-objective FFA (Moffa) is lower than that of the multi-objective HHO (Mohho) algorithm.…”
Section: Introductionmentioning
confidence: 99%